Cibalackrot Dendrimers for Hyperfluorescent Organic Light‐Emitting Diodes. Issue 16 (12th April 2022) - Wallwork, Nicholle R.; Mamada, Masashi; Keto, Angus B.; McGregor, Sarah K. M.; Shukla, Atul; Adachi, Chihaya; Krenske, Elizabeth H.; Namdas, Ebinazar B.; Lo, Shih‐Chun
Abstract: Hyperfluorescent organic light‐emitting diodes (HF‐OLEDs) enable a cascading Förster resonance energy transfer (FRET) from a suitable thermally activated delayed fluorescent (TADF) assistant host to a fluorescent end‐emitter to give efficient OLEDs with relatively narrowed electroluminescence compared to TADF‐OLEDs. Efficient HF‐OLEDs require optimal FRET with minimum triplet diffusion via Dexter‐type energy transfer (DET) from the TADF assistant host to the fluorescent end‐emitter. To hinder DET, steric protection of the end‐emitters has been proposed to disrupt triplet energy transfer. In this work, the first HF‐OLEDs based on structurally well‐defined macromolecules, dendrimers is reported. The dendrimers contain new highly twisted dendrons attached to a Cibalackrot core, resulting in high solubility in organic solvents. HF‐OLEDs based on dendrimer blend films are fabricated to show external quantum efficiencies of >10% at 100 cd m −2 . Importantly, dendronization with the bulky dendrons is found to have no negative impact to the FRET efficiency, indicating the excellent potential of the dendritic macromolecular motifs for HF‐OLEDs. To fully prevent the undesired triplet diffusion, Cibalackrot dendrimers HF‐OLEDs are expected to be further improved by adding additional dendrons to the Cibalackrot core and/ or increasing dendrimer generations. Abstract : 1 st‐ Generation Cibalackrot dendrimers with new highly‐twisted mesityl dendrons are synthesized, enabling high solubility and low aggregates in blend films. Hyperfluorescent dendrimer organic light‐emitting diodes (OLEDs) are first demonstrated to process external quantum efficiencies (EQEs) of >10% (@ 100 cd m −2 ), high current densities (>200 mA cm −2 ), and low EQE roll‐off, showing potential of dendritic fluorescent macromolecules for efficient hyperfluorescent OLEDs.